In Vitro And In Vivo Effects Of Bisphenol A On Cell Growth, Lipid Accumulation And Inflammation In Liver Cell Line, Rat Adipose And Colorectal Tissues - Ismael, Ismael Layla Qasim (2024)
Bisphenol A (BPA) is an exogenous endocrine disruptor that mimics hormones closely associated with health complications, such as cancer progression. BPA is also linked to an increase in the prevalence of obesity and obesity-related diseases due to its obesogenic action. The present study aimed to evaluate the effects of BPA on human liver cells and animal tissues. The BPA-treated THLE-2 cell viability was first evaluated using an MTT assay. Cytoplasmic lipid accumulation was then examined in the BPA-treated THLE-2 cells using Oil Red O staining. The expression of various adipogenesis genes in lipid metabolism, including clusterin, PPARs, CYPs, UCP1, and BRS3 in BPA-treated THLE‑2 cells, was investigated using real-time PCR. Subsequently, flow cytometry measured the DNA synthesis in BPA-treated THLE-2 cells was performed using BrdU/PI staining. The pro-inflammatory proteins IL6 and CCL2 in the conditioned media and cytoplasmic proteins of the BPA-treated THLE-2 cells were examined by ELISA. After that, various adipogenesis genes’ expression in lipid metabolism, including clusterin, PPARs, CYPs, UCP1 and BRS3, in adipose and colorectal tissues of the rats fed a diet (normal or high fat) supplemented with and without BPA was investigated using real-time PCR.